Rust-free solvent-free anticorrosive paint as well as preparation method and use method thereof

By developing solvent-free anti-corrosion coatings and using epoxy resins and other additives, traditional coatings have solved the problems of difficulty in removing rust, solvent pollution and poor anti-corrosion effects in the field of tower anti-corrosion, and achieved efficient and environmentally friendly anti-corrosion effects and construction efficiency.

CN119529635AInactive Publication Date: 2025-02-28CHINA TOWER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411656226.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional anticorrosion coatings have problems such as difficulty in removing rust, volatile solvent pollution, high construction costs and poor anticorrosion effects in the field of tower anti-corrosion.

Method used

A solvent-free anti-corrosion coating was developed, using epoxy resin bisphenol A and bisphenol F as the main agent, combining toughening agents, cashew phenol glycidyl ether, anti-rust pigment and additives to form a coating with high adhesion and anti-corrosion properties.

Benefits of technology

This coating significantly simplifies the construction process, reduces construction difficulty and cost, avoids volatile solvent pollution, and improves the anti-corrosion performance and service life of the tower.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of anti-corrosion coatings, in particular to a rust-free solvent-free anti-corrosion coating and a preparation method and using method.The rust-free solvent-free anti-corrosion coating comprises a main agent and a curing agent, the main agent comprises epoxy resin bisphenol A resin, epoxy resin bisphenol F resin, a toughening agent, cardanol glycidyl ether, anti-rust pigment, pigment filler, body filler, a rust conversion agent and auxiliaries, wherein the mass ratio of the epoxy resin bisphenol A resin to the epoxy resin bisphenol F resin in the main agent is 30-60%, and the mixing mass ratio of the epoxy resin bisphenol A resin to the epoxy resin bisphenol F resin is (2-3): 1. The rust-removal-free solvent-free anticorrosive paint has very strong binding force and infiltration capacity to a low-surface-treatment base material, forms a compact shielding coating, and can effectively prevent water and salt mist from permeating into the rust-removal-free solvent-free anticorrosive paint. And the anti-rust pigment and the rust conversion agent have a synergistic effect, and can generate passivation reaction and complexation reaction with a rusted object to generate a layer of compact and stable protective film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a rust-free solvent-free anti-corrosion coating, a preparation method thereof and a use method thereof. Background Art

[0002] In today's communication and power transmission fields, iron towers play a key role as important infrastructure. However, due to long-term exposure to various harsh outdoor environmental conditions, such as air pollution, humidity changes, acid rain erosion, etc., the metal structure of the iron tower is very susceptible to corrosion.

[0003] Traditional anti-corrosion treatment methods for iron towers usually require tedious and laborious rust removal procedures. In the actual maintenance and construction of iron towers, rust removal often faces many difficulties. For example, the iron tower structure is complex, high-altitude operations are difficult, and rust removal is inconvenient; and large-scale rust removal is not only time-consuming, but also significantly increases maintenance costs.

[0004] In addition, the volatilization of organic solvents in the existing solvent-based anti-corrosion coatings during use will pollute the environment and pose a potential threat to the health of construction workers. Moreover, solvent-based coatings may shrink and crack during the drying process, affecting the anti-corrosion effect.

[0005] In the field of iron tower anti-corrosion, due to its special location and structural characteristics, the performance requirements for anti-corrosion coatings are extremely high. Traditional coatings often require multiple coatings to achieve the ideal anti-corrosion effect, which not only increases the construction cost, but also may affect the normal use of the iron tower due to the long construction period.

[0006] Therefore, in response to the anti-corrosion needs of iron towers, it is urgent to develop a new type of rust-free and solvent-free anti-corrosion coating and its preparation method, which is of great significance for improving the service life of iron towers, reducing maintenance costs, and ensuring the stable transmission of communications and electricity. Summary of the invention

[0007] One of the purposes of the present invention is to provide a rust-free solvent-free anti-corrosion coating, which avoids the pollution to the environment caused by the volatilization of organic solvents and the harm to the health of construction workers, meets modern environmental protection requirements, can significantly enhance the adhesion and anti-corrosion performance of the coating on the metal surface of the iron tower, effectively resists adverse environmental factors such as air pollution, humidity changes, acid rain erosion, and prolongs the service life of the iron tower.

[0008] The second object of the present invention is to provide a method for preparing a rust-free solvent-free anti-corrosion coating, which has a simple preparation process and is easy to adjust.

[0009] The third purpose of the present invention is to provide a method for using a rust-free solvent-free anti-corrosion coating, thereby simplifying the construction process and reducing construction difficulty and cost.

[0010] The scheme adopted by the present invention to achieve one of the purposes is: a rust-free solvent-free anti-corrosion coating, comprising a main agent and a curing agent, wherein the main agent comprises epoxy resin bisphenol A resin, epoxy resin bisphenol F resin, a toughening agent, cardanol glycidyl ether, an anti-rust pigment, a color filler, a system filler, a rust conversion agent, and an auxiliary agent, wherein the mass proportion of epoxy resin bisphenol A resin and epoxy resin bisphenol F resin in the main agent is 30%-60%, and the mixed mass ratio of epoxy resin bisphenol A resin and epoxy resin bisphenol F resin is 2-3:1.

[0011] The main agent adopts low molecular weight epoxy resin as bisphenol A resin and bisphenol F resin. Due to the presence of a large amount of polar groups such as hydroxyl and ether groups in the epoxy resin molecular structure, in the cross-linking curing process, the active hydroxyl in the molecule reacts with the interface metal substrate atoms to form a very stable chemical bond, which ensures that the cured coating and the metal substrate have extremely strong adhesion. In addition, the rigid benzene ring structure in the high cross-linking density and the molecular chain makes the coating have excellent physical and mechanical properties such as wear resistance, impact resistance, impact resistance, and scratch resistance. In this preferred embodiment, due to the low viscosity of bisphenol F resin, bisphenol A resin and bisphenol F resin are mixed according to a certain mass ratio, which can effectively improve the viscosity of the solvent-free anticorrosive coating system, and is convenient for on-site construction spraying operations. Wherein epoxy resin bisphenol A resin and bisphenol F resin account for 30%-60% in the main agent mass, and the mixed mass ratio of bisphenol A resin and bisphenol F resin is 2-3:1.

[0012] Preferably, the epoxy equivalent of the epoxy resin bisphenol A resin is 184-190, and the epoxy equivalent of the epoxy resin bisphenol F resin is 160-180.

[0013] Preferably, the toughening agent is epoxy-modified polysulfide EPS25 toughening resin, which accounts for 3%-7% by weight in the main agent; the cardanol glycidyl ether is Cardolite NC-547 cardanol glycidyl ether, which accounts for 5%-10% by weight in the main agent.

[0014] In the above-mentioned rust-free solvent-free anti-corrosion coating, due to the relatively high cross-linking density of low molecular weight epoxy resin, the molecular chain segment is short and the movement is restricted, which makes it difficult to absorb energy by stretching and slipping of the molecular chain when subjected to external force, thereby showing brittleness. In order to improve the brittleness of the paint film, a toughening agent is used. The present invention uses Beijing Tianhengjian's epoxy-modified polysulfide EPS25 toughening resin as a toughening agent, which contains polysulfide compounds with -SH functional groups and low molecular weight compounds with epoxy functional groups. After addition, it can be well compatible with epoxy resin, significantly improving the flexibility, sealing, aging resistance, chemical corrosion resistance, etc. of the coating. The amount of epoxy-modified polysulfide EPS25 added in the main agent accounts for 3%-7% by mass.

[0015] In the above-mentioned rust-free solvent-free anti-corrosion coating, a certain amount of cardanol glycidyl ether is added, which can further improve the flexibility, impact resistance, wear resistance and acid and alkali resistance of the coating. Cardanol glycidyl ether is a flexible bifunctional glycidyl ether. Its carbon 8 side chain separates the aromatic ring group and can be well compatible with the resin, increasing its flexibility, impact resistance, wear resistance and acid and alkali resistance. The present invention selects Cardol NC-547 cardanol glycidyl ether, which accounts for 5%-10% by mass in the main agent.

[0016] Preferably, the anti-rust pigment is compounded with zinc phosphate, aluminum tripolyphosphate, zinc molybdate and / or titanium phosphate, and the mass ratio of the anti-rust pigment in the main agent is 5%-20%; when three compounds are used, the mass ratio of zinc phosphate, aluminum tripolyphosphate, zinc molybdate or titanium phosphate is 1:1-2:2-3; when four compounds are used, the mass ratio of zinc phosphate, aluminum tripolyphosphate, zinc molybdate and titanium phosphate is 1:1-2:1-3:1-4.

[0017] In the above-mentioned rust-free solvent-free anti-corrosion coating, in order to ensure that the coating can be applied on the surface of the rusty substrate, the sandblasting and rust removal process is eliminated, and the coating has good anti-corrosion performance, an anti-rust pigment is added to the coating. The anti-rust pigment can react chemically with the rust layer to generate a stable compound, so that the entire rust layer becomes a part of the filler in the coating. The present invention is compounded with zinc phosphate, aluminum tripolyphosphate, zinc molybdate and / or titanium phosphate, and zinc phosphate, aluminum tripolyphosphate and zinc molybdate, titanium phosphate, three or more of which are mixed and compounded in a certain proportion, wherein titanium phosphate and aluminum tripolyphosphate can react chemically with the surface of the rusty metal to generate a layer of stable phosphate protective film. This protective film can block the direct contact between the corrosive medium and the metal, thereby slowing down the corrosion process. The tripolyphosphate ions in aluminum tripolyphosphate can exchange and complex with the harmful ions in the corrosive medium, fix them inside the pigment, and reduce the erosion of the metal. In the presence of water and oxygen, zinc phosphate and titanium phosphate will form a firmly attached complex precipitation film on the rusty substrate, which plays a corrosion inhibition role. It can be used as a cathodic anti-rust pigment to inhibit the cathode reaction, thereby reducing the corrosion rate of the metal. Zinc molybdate and zinc phosphate particles can fill the pores and defects in the coating, forming a physical shielding layer to prevent the penetration of corrosive media. Aluminum tripolyphosphate and zinc phosphate work synergistically through multiple mechanisms, which can effectively improve the corrosion resistance and durability of the coating on rusty substrates.

[0018] Preferably, when zinc molybdate and / or titanium phosphate are used, modification treatment is required, and the specific modification treatment process is as follows: S1: First, the raw material to be modified is mixed with anhydrous ethanol and stirred to hydroxylate the surface of the raw material to be modified: S2: then add the silane coupling agent into anhydrous ethanol and mix evenly; then mix with the solution of step S1 and stir at 55-65° C. until the reaction is complete; S3: drying the mixed solution after the reaction in step S2 is completed, and grinding and sieving the solid residue obtained after drying.

[0019] In the mixed anti-rust pigments used above, although zinc phosphate and aluminum tripolyphosphate can be well dispersed in the resin and are compatible with bisphenol A resin and bisphenol F resin, zinc molybdate and titanium phosphate, when used in combination with zinc phosphate and aluminum tripolyphosphate, have poor miscibility with bisphenol A resin and bisphenol F resin, and there are certain gaps inside the paint film, which ultimately leads to poor density and anti-permeability of the coating, so zinc molybdate and titanium phosphate need to be further modified.

[0020] It adopts zinc phosphate, aluminum tripolyphosphate, modified zinc molybdate and modified titanium phosphate as a mixture to exert their synergistic effect. The particle size is about 800-1200 mesh, accounting for 5%-20% by mass in the main agent. It has the best anti-rust performance and anti-penetration ability.

[0021] Preferably, the pigment filler is one or more of mica powder, aluminum silver paste, and iron red, and the mass proportion of the pigment filler in the main agent is 10%-30%; the system filler is one or more of talcum powder, barium sulfate, and silicon micropowder, with a particle size of 600-1500 mesh, and the total mass added ratio in the main agent is 10%-35%.

[0022] Adding a certain amount of one or more pigments and fillers such as mica powder, aluminum silver paste, iron red, etc. can further improve the shielding and anti-corrosion properties of the coating, and the mass proportion in the main agent is 10%-30%.

[0023] In order to increase the solid content of the rust-free solvent-free anti-corrosion coating system, reduce the coating cost, and improve the hardness and wear resistance of the coating, a certain amount of system filler is added, namely one or more of talcum powder, barium sulfate, silica powder, etc., with a particle size of approximately 600 mesh-1500 mesh, and the total mass added to the main agent is 10%-35%.

[0024] Preferably, the auxiliary agent is one or more of a rheological auxiliary agent, a rust conversion agent, a dispersant, a leveling agent, a defoaming agent, and a silane coupling agent, and the weight proportion of the auxiliary agent in the main agent is 3%-15%.

[0025] The additives are mainly rheological additives, one or more of rust converters, dispersants, leveling agents, defoamers, and silane coupling agents. The mass proportion of additives in the main agent is 3%-15%.

[0026] Preferably, the rheological additive is mainly selected from Deqian's polyamide wax THIXATROL MAX and Evonik's hydrophobic fumed silica 972. The two are mixed in a certain proportion and used synergistically to effectively improve the rheology and storage properties of the coating. The mass proportion of the rheological additive in the main agent is 0.35%-1.1%, and the mass ratio of polyamide wax THIXATROL MAX and fumed silica 972 is 4:1-1:1.

[0027] Preferably, the rust conversion agent is a mixture of one or more of tannic acid, phosphoric acid, organic oxalic acid, gallic acid, and citric acid. Tannic acid, gallic acid, and citric acid can react with rust to form a protective film. Phosphoric acid and organic oxalic acid can react chemically with rust to form a stable phosphate coating, which plays a role in rust prevention and rust conversion. In addition, they have good chelating properties and can combine with metal ions in rust to achieve rust conversion and protection. The present invention has been proved by a large number of experiments that the amount of rust conversion agent added cannot be too large. More rust conversion agents will not only be corrosive to the metal substrate, but also have a certain effect on the water resistance, alkali resistance, salt spray resistance and adhesion of the coating. The rust conversion agent is mixed and used with a variety of acids to exert its synergistic effect. The mass proportion in the main agent is 0.5%-2%, and its anti-rust performance is the best.

[0028] Preferably, the dispersant is mainly selected from one or more of BYK111, BYK 2013, and BYK 2062, and the mass proportion of the dispersant in the main agent is 0.5%-2%.

[0029] Preferably, the leveling agent is mainly selected from one or more of BYK358N, BYK 361N, and BYK 356, and the mass proportion of the leveling agent in the main agent is 0.3%-2%.

[0030] Preferably, the defoaming agent is mainly selected from one or more of BYK 066N, BYK A530, and EFKA-2022, and the mass proportion of the defoaming agent in the main agent is 0.1%-1%.

[0031] Preferably, the silane coupling agent is mainly selected from one or more of Dow Corning's Z-6040 and Momentive A187, and the mass proportion of the silane coupling agent in the main agent is 0.5%-2%.

[0032] Preferably, the curing agent is cashew oil-modified phenolic amine, and the mass ratio of the main agent to the curing agent is 3-5:1.

[0033] Curing agent selects cashew nut oil modified phenolic amine, with unsaturated double bond carbon 15 long chain in the curing agent, after cross-linking curing reaction with epoxy resin bisphenol A resin and bisphenol F resin, curing shrinkage is small, and its coating structure is extremely dense, so that the coating has excellent acid resistance, alkali resistance, fresh water immersion resistance, seawater immersion resistance, salt spray resistance and cathode stripping resistance and other corrosion resistance characteristics, even in severe corrosive environment, metal substrate corrosion resistance still has ultra-long durability. In addition, cashew nut oil modified phenolic amine can be well penetrated in the rusty substrate and compatible with it, showing excellent adhesion. The present invention selects one or more of Cardolite's cashew nut oil modified phenolic amine NX-5653, Wansheng shares cashew nut oil modified phenolic amine WSCM-1103, and Shanghai Meidong cashew nut oil modified phenolic amine 641L. The mass ratio of the main agent and the curing agent is 3: 1-5: 1.

[0034] The solution adopted by the present invention to achieve the second purpose is: a method for preparing the rust-free solvent-free anti-corrosion coating, the method for preparing the main agent comprises the following steps: (1) First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, toughening agent and cardanol glycidyl ether evenly, and disperse at a low speed (500r / min-800r / min) for 20-30min; (2) Add anti-rust pigment, pigment filler, and system filler in sequence and disperse at high speed until the fineness is ≤80μm; disperse at high speed (1700r / min-2000r / min) for 1-2 hours; (3) Finally, add the auxiliary agent and disperse evenly, disperse at low speed (500r / min-800r / min) for 20-30min, and filter to obtain the main agent.

[0035] Alternatively, the rheological additive may be added first in step (2) and the remaining additives may be added in step (3).

[0036] The solution adopted by the present invention to achieve the third purpose is: a method for using the rust-free solvent-free anti-corrosion coating, comprising the following steps: mixing the main agent and the curing agent in a mass ratio of 3-5:1, and spraying or brushing them on the metal surface to be treated.

[0037] The use of the rust-free solvent-free anti-corrosion coating of the present invention significantly simplifies the anti-corrosion construction process of the iron tower: there is no need to carry out complicated rust removal treatment, which greatly simplifies the construction process, reduces the construction difficulty and cost, especially for high places and complex structural parts of the iron tower, reduces the construction difficulty and danger, and saves a lot of manpower and time costs.

[0038] The rust-free solvent-free anti-corrosion coating of the present invention has excellent environmental protection performance: it avoids the pollution to the environment caused by the volatilization of organic solvents and the harm to the health of construction workers, and meets modern environmental protection requirements.

[0039] The rust-free solvent-free anti-corrosion coating of the present invention has excellent anti-corrosion performance: it significantly enhances the adhesion and anti-corrosion performance of the coating on the metal surface of the iron tower, can form a strong and dense protective layer on the surface of the iron tower, effectively blocking the contact of moisture, oxygen, corrosive substances and the like in the atmosphere with the metal, can effectively resist severe environmental factors such as air pollution, humidity changes, acid rain erosion, etc., significantly improves the corrosion resistance of the iron tower in harsh environments, and greatly extends the service life of the iron tower.

[0040] The rust-free solvent-free anti-corrosion coating of the present invention has high construction efficiency: it can reduce the number of times the coating is applied, shorten the construction period, improve construction efficiency, enable the iron tower to resume normal use more quickly, and reduce the impact of anti-corrosion construction on communications and power transmission.

[0041] The rust-free solvent-free anti-corrosion coating of the present invention has good stability: the coating is stable in nature during storage and transportation and is not easy to deteriorate, thereby ensuring the quality of the coating and the stability of the anti-corrosion effect, and is convenient for application in anti-corrosion projects of iron towers under different construction conditions.

[0042] The use of the rust-free solvent-free anti-corrosion coating of the present invention is economical and practical: considering the construction cost, maintenance cost and the extension of the service life of the iron tower, the coating of the present invention has a high cost performance ratio and brings significant economic benefits to the field of iron tower anti-corrosion.

[0043] The present invention has the following advantages and beneficial effects: The rust-free solvent-free anti-corrosion coating of the present invention has strong bonding and penetration capabilities for low surface treatment substrates, such as floating rust, flash rust, scale, and substrates with severe rust. That is, it can fully wet and penetrate the loose and porous rust layer, tightly wrap the rust layer, and form a dense barrier coating, which can effectively prevent water and salt spray from penetrating therein.

[0044] The rust-free solvent-free anticorrosive coating of the present invention contains an antirust pigment and a rust converter, which play a synergistic role and can produce a passivation reaction and a complex reaction with rusted materials to form a dense and stable protective film.

[0045] The solvent-free anti-corrosion coating prepared by the present invention has high solid content, almost no VOC emission, is environmentally friendly, can obtain a high film thickness by one coating, has strong wettability and permeability, and still has excellent adhesion and anti-corrosion performance even on a rusty substrate. DETAILED DESCRIPTION

[0046] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0047] In the following examples, unless otherwise specified, all methods are conventional methods; the reagents and materials described, unless otherwise specified, can be obtained from commercial sources.

[0048] Example 1

[0049] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mixed anti-rust pigment, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add rust converter, dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0050] Preferably, the curing agent is Cardolite's cashew oil modified phenolic amine NX-5653. After the main agent and the curing agent are evenly mixed in a mass ratio of 3:1, the coating is evenly applied on the rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0051] Example 2

[0052] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mixed anti-rust pigment, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add rust converter, dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0053] Preferably, the curing agent is Wansheng Co., Ltd.'s cashew oil-modified phenolic amine WSCM-1103. After the main agent and the curing agent are evenly mixed in a mass ratio of 4:1, the coating is evenly applied on the rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0054] Example 3

[0055] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mixed anti-rust pigment, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add rust converter, dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0056] Preferably, the curing agent is Shanghai Meidong cashew oil modified phenolic amine 641L. After the main agent and the curing agent are evenly mixed in a mass ratio of 5:1, the coating is evenly applied on a rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0057] Comparative Example 1

[0058] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, and silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0059] Preferably, the curing agent is Cardolite's cashew oil modified phenolic amine NX-5653. After the main agent and the curing agent are evenly mixed in a mass ratio of 3:1, the coating is evenly applied on the rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0060] Comparative Example 2

[0061] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mixed anti-rust pigment, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add mixed anti-rust pigment, dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0062] Preferably, the curing agent is Cardolite's cashew oil modified phenolic amine NX-5653. After the main agent and the curing agent are evenly mixed in a mass ratio of 3:1, the coating is evenly applied on the rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0063] Comparative Example 3

[0064] Preferably, the preparation process of the main agent is as follows: First, mix epoxy resin bisphenol A, epoxy resin bisphenol F, epoxy modified polysulfide EPS25, and cardanol glycidyl ether evenly, disperse at low speed (500r / min-800r / min) for 20-30min, then add polyamide wax THIXATROL MAX, hydrophobic fumed silica 972, mixed anti-rust pigment, mica powder, aluminum silver paste, iron red, talcum powder, barium sulfate in turn, disperse at high speed (1700r / min-2000r / min) for 1-2 hours, and when the fineness is ≤80μm, finally add mixed acid rust converter, dispersant BYK2013, leveling agent BYK361N, defoamer BYK066N, silane coupling agent Z-6040, disperse at low speed (500r / min-800r / min) for 20-30min, and filter through a filter to obtain the main agent.

[0065] Preferably, the curing agent is Cardolite's cashew oil modified phenolic amine NX-5653. After the main agent and the curing agent are evenly mixed in a mass ratio of 3:1, the coating is evenly applied on the rusty carbon steel plate by high-pressure airless spraying or brushing. After curing at room temperature for 14 days and the coating is completely cured, its performance is tested.

[0066] The coatings prepared in Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, Comparative Example 3 were tested for performance, and the test items and results are shown in the table:

[0067] From the above test results, it can be seen that in terms of corrosion resistance such as acid resistance, alkali resistance, oil resistance, fresh water resistance, seawater resistance, salt spray resistance, seawater immersion resistance, and ultraviolet aging resistance, the corrosion resistance data of Example 1, Example 2, and Example 3 prepared by the present invention are better than those of Comparative Example 1, Comparative Example 2, and Comparative Example 3. This is because a certain amount of mixed anti-rust pigments and rust converters are added to Example 1, Example 2, and Example 3, while Comparative Example 1 does not have any mixed anti-rust pigments and rust converters, Comparative Example 2 only has mixed anti-rust pigments, and Comparative Example 3 only has mixed acid rust converters.

[0068] In Comparative Examples 1, 2 and 3, the mixed anti-rust pigments such as aluminum tripolyphosphate, zinc phosphate modified zinc molybdate, and modified titanium phosphate synergistically work together through various mechanisms to generate stable compounds with rust products, that is, to form a passivation protective film, which can block the direct contact between the corrosive medium and the metal substrate, thereby slowing down the corrosion process. Rust converters such as tannic acid, phosphoric acid, organic oxalic acid, gallic acid, citric acid and other acid mixtures can react chemically with rust to generate a stable acid salt coating, which plays a role in converting rust, thereby stabilizing the rust and preventing it from corroding and spreading. The use of aluminum tripolyphosphate, zinc phosphate modified zinc molybdate, modified titanium phosphate and the like in combination with mixed acids can exert a synergistic effect and effectively improve the corrosion resistance of rusted metal substrates.

[0069] The rust-free solvent-free anti-corrosion coating of the present invention is coated on a rusty substrate and still exerts its excellent anti-corrosion performance even in a harsh environment of high salt fog and high ultraviolet light. This has great practical value for improving the anti-corrosion durability and stability of the rusty metal substrate.

[0070] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A rust-free solvent-free anti-corrosion coating, characterized in that: The invention comprises a main agent and a curing agent, wherein the main agent comprises epoxy resin bisphenol A resin, epoxy resin bisphenol F resin, a toughening agent, cardanol glycidyl ether, an anti-rust pigment, a color filler, a system filler, a rust conversion agent, and an auxiliary agent, wherein the mass proportion of epoxy resin bisphenol A resin and epoxy resin bisphenol F resin in the main agent is 30%-60%, and the mixed mass ratio of epoxy resin bisphenol A resin and epoxy resin bisphenol F resin is 2-3:

1.

2. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The epoxy equivalent of the epoxy resin bisphenol A resin is 184-190, and the epoxy equivalent of the epoxy resin bisphenol F resin is 160-180.

3. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The toughening agent is epoxy modified polysulfide EPS25 toughening resin, which accounts for 3%-7% by weight in the main agent; the cardanol glycidyl ether is Cardolite NC-547 cardanol glycidyl ether, which accounts for 5%-10% by weight in the main agent.

4. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The anti-rust pigment is compounded with zinc phosphate, aluminum tripolyphosphate, zinc molybdate and / or titanium phosphate, and the mass ratio of the anti-rust pigment in the main agent is 5%-20%; when three compounds are used, the mass ratio of zinc phosphate, aluminum tripolyphosphate, zinc molybdate or titanium phosphate is 1:1-2:2-3; when four compounds are used, the mass ratio of zinc phosphate, aluminum tripolyphosphate, zinc molybdate and titanium phosphate is 1:1-2:1-3:1-4.

5. The rust-free solvent-free anti-corrosion coating according to claim 4, characterized in that: When zinc molybdate and / or titanium phosphate are used, modification treatment is required. The specific modification process is as follows: S1: First, the raw material to be modified is mixed with anhydrous ethanol and stirred to hydroxylate the surface of the raw material to be modified: S2: then add the silane coupling agent into anhydrous ethanol and mix evenly; then mix with the solution of step S1 and stir at 55-65° C. until the reaction is complete; S3: drying the mixed solution after the reaction in step S2 is completed, and grinding and sieving the solid residue obtained after drying.

6. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The pigment filler is one or more of mica powder, aluminum silver paste, and iron red, and the mass proportion of the pigment filler in the main agent is 10%-30%; the system filler is one or more of talcum powder, barium sulfate, and silicon micropowder, with a particle size of 600-1500 mesh, and the total mass addition ratio of the pigment filler in the main agent is 10%-35%.

7. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The rust conversion agent is a mixture of one or more of tannic acid, phosphoric acid, organic oxalic acid, gallic acid, and citric acid; the auxiliary agent is one or more of a rheological additive, a rust conversion agent, a dispersant, a leveling agent, a defoaming agent, and a silane coupling agent; and the mass proportion of the auxiliary agent in the main agent is 3%-15%.

8. The rust-free solvent-free anti-corrosion coating according to claim 1, characterized in that: The curing agent is cashew oil modified phenolic amine, and the mass ratio of the main agent to the curing agent is 3-5:

1.

9. A method for preparing a rust-free solvent-free anti-corrosion coating as claimed in any one of claims 1 to 8, characterized in that: The preparation method of the main agent comprises the following steps: (1) First, epoxy resin bisphenol A, epoxy resin bisphenol F, toughening agent and cardanol glycidyl ether are mixed uniformly; (2) Add anti-rust pigment, pigment filler, and system filler in sequence and disperse at high speed until the fineness is ≤80μm; (3) Finally, add the auxiliary agent and disperse it evenly, then filter to obtain the main agent.

10. A method for using the rust-free solvent-free anti-corrosion coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the main agent and the curing agent in a mass ratio of 3-5:1 evenly, and then spraying or brushing the mixture on the rusty metal surface.

Citation Information

Patent Citations

  • Epoxy anticorrosive paint for underwater steel

    CN102719174A

  • Solvent-free epoxy antirust coating capable of coating with rust and preparation method thereof

    CN104017458A

  • Stable permeation composite type rust coating and preparation method thereof

    CN105885631A

  • Solvent-less epoxy anti-corrosive paint

    CN107384129A

  • Solvent-free heavy anti-corrosion coating capable of being coated with water and rust and preparation method of solvent-free heavy anti-corrosion coating

    CN115011213A